1994
DOI: 10.1002/gcc.2870090103
|View full text |Cite
|
Sign up to set email alerts
|

Loss of chromosome band 8q24 in sporadic osteocartilaginous exostoses

Abstract: We have karyotyped eight sporadic osteocartilaginous exostoses (OCE), a tumor type not characterized cytogenetically before. Five tumors had only normal karyotypes, whereas three displayed the following abnormal karyotypes: 46,XY,del(8)(q24.1); 46,XX,del(8)(q22), t(8;14)(q24.1;q32); and 46,XY,der(8)t(1;8)(q21;q24),inv(12)(p11q13). All three aberrant cases thus had structural rearrangements leading to loss of the distal part of 8q. This is of particular interest because multiple OCE are part of the disease phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 23 publications
(20 reference statements)
2
31
1
Order By: Relevance
“…Osteochondromas often show normal cytogenetics with loss of heterozygosity (LOH) at the EXT1 and EXT2 loci as the most characteristic aberrations (Bovée et al, 1999). However, some cytogenetic alterations have been detected, suggesting a clonal neoplastic growth (Mertens et al, 1994). In contrast, osteosarcomas are often characterized by an array of sequential and well-orchestrated genetic changes, with complex and heterogeneous chromosomal abnormalities (Sandberg and Bridge, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Osteochondromas often show normal cytogenetics with loss of heterozygosity (LOH) at the EXT1 and EXT2 loci as the most characteristic aberrations (Bovée et al, 1999). However, some cytogenetic alterations have been detected, suggesting a clonal neoplastic growth (Mertens et al, 1994). In contrast, osteosarcomas are often characterized by an array of sequential and well-orchestrated genetic changes, with complex and heterogeneous chromosomal abnormalities (Sandberg and Bridge, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…56 During malignant transformation additional genetic alterations are obtained, 5 probably causing defects in mitotic checkpoints leading to chromosomal instability which in turn may cause aneuploidy including near-haploidy. 60 In osteochondromas near-haploidy is absent 61,62 and near-haploidy can therefore be considered a progression marker toward a low-grade malignant phenotype. Our results suggest that further progression toward highgrade chondrosarcoma is characterized by polyploidization.…”
Section: Discussionmentioning
confidence: 99%
“…However, later studies detected cytogenetic aberrations suggesting that loss or mutation of EXT1 and EXT2 are important in the pathogenesis of sporadic as well as hereditary osteochondromas, thus indicating the neoplastic origin of these lesions (Mertens et al, 1994;Bridge et al, 1998). In 1995, two separated studies found loss of heterozygosity for markers linked to EXT1 and EXT2, and suggested that osteochondromas development follows the Knudson's two-hit model for tumor suppressor gene inactivation Raskind et al, 1995).…”
Section: Introductionmentioning
confidence: 99%